Urban Trees at UNIMAS East Campus and UiTM Campus - Lim, Soo Pheng. (Universiti Malaysia Sarawak (UNIMAS), 2007)
Biodiversity IS an indicator of the health of urban forest. It is recommends that U1 mban fore stry there must no more than 10% of the trees be from anyone species. A broader diversity of trees IS needed in urban forest to guard aga in st large sca le of devastation by msect and pest diseases. A sW'vey was earned oul (0 assess the level of urban tree diversity a l Unimas East campus and UITM campus. Species diversity index (SDI) of Unimas East campus and UiTM campus was 2.S 1 and 8.06 respec tivel y. The latter was conSidered high compare to otJlers Asean country. A lotal of 262 crees and 264 Lrees at Unlmas East campus and UiTM campus were enumerated in 10 plots of 20m x 20m . There were 16 species from 10 familie s at Unimas East campus and 21 species from 15 familIes at UiTM campus. Andira slirinamemis (Bondt) Splitg. ex Pulle and Syzygium grande were the most abundant specIes eono·ibuting the highest carbon storage o f 38058.47 kg and 16795.40 kg at Unlmas East campus and UiTM campus respectivel y. The recommended speCIes and va lldilY of blOmass regression equatIon was discussed.